Perkinsus Infections of Bivalve Molluscs - Denise Petty (EDIS)
FA178, a 6-page fact sheet by Denise Petty, describes the infections caused by this group of protistan parasites that can infect shellfish — signs of infection in molluscs, life cycle, transmission, diagnosis, regulatory concerns, treatment and disinfection of facilities, and food safety. Includes references and glossary. Published by the UF Department of School of Forest Resources and Conservation, November 2010.